Ocular toxicity events of cyclin-dependent kinase 4/6 inhibitors in breast cancer: a pharmacovigilance study based on the faers database - Zhang, Mengdi; Pu, Dongqing; Yu, Minmin; Shi, Guangxi; Li, Jingwei (Frontiers in Pharmacology, 2025)
BackgroundBased on the FDA Adverse Event Reporting System (FAERS) database, this study aims to explore signals of ocular-related adverse events associated with cyclin-dependent kinase 4/6 inhibitors (CDK4/6 inhibitors), providing a reference for clinical medication safety.MethodsData on ocular adverse events (OAEs) related to CDK4/6 inhibitors from the 1st quarter of 2015 to the 3rd quarter of 2024 were downloaded from the official website of the FAERS database. The ROR, PRR, and BCPNN methods were employed to evaluate the correlation between CDK4/6 inhibitors and OAEs. A disproportionality analysis was conducted to assess the risk of ocular toxicity. Multivariate logistic regression analysis was used to explore influencing factors. Data processing, analysis and visualization were performed using R software.ResultsA total of 1974 OAEs reports were associated with CDK4/6 inhibitors, including 86 for Abemaciclib, 1,449 for Palbociclib, and 439 for Ribociclib. This study identified 66 OAEs signals related to CDK4/6 inhibitors. Myopia accounted for the highest proportion of serious cases (57.14%), while Glaucoma had the highest proportion of death cases (13.64%). There were 41 positive signals, among which Dark circles under eyes, Eye disorder, Cataract, and Blindness posed significant risks. Multivariate logistic regression analysis revealed that Ribociclib showed higher ocular toxicity than Abemaciclib (P < 0.05).ConclusionThe current study supports concerns about the risk of OAEs when breast cancer patients use CDK4/6 inhibitors. Clinicians should raise awareness, conduct multidisciplinary assessments/management, and remind patients to pay attention to clinical symptoms. The potential differences among CDK4/6 inhibitors deserve further investigation.